Next-generation power converter design using wide bandgap power devices - Shang, Shuye (Nanyang Technological University, 2023)
Silicon-based semiconductor power switching devices have reached their performance limits. In order to meet the energy concept of sustainable development and low-carbon society, we need to further improve the power switching characteristics by researching breakthrough technologies. This study focuses on the wide bandgap (WBG) power devices such as SiC MOSFETs which have the superior electrical characteristics, providing new opportunities for the design of next-generation ultra-high efficiency and ultra-high power density power converters. This project analyzes the power switch tube process and the latest high-frequency switching WBG technology through a multidisciplinary approach to facilitate the design of WBG-based power converters in terms of energy efficiency, power density, and operational reliability.